Improving Resource Efficiency and Minimize Environmental Footprint - a case study preliminary results - M. T. D. Albuquerque (2017)
Panasqueira Mine (Portugal) has been mainly exploited for wolframite, cassiterite andchalcopyrite (W, Sn, Cu). Through the detailed and careful characterization of tailings with differentmineralogy, new invaluable insights into the weathering characteristics of many different minerals willbe received, making possible proper risk assessments, and predict which type of tailings might posesevere future environmental risk namely to the Zêzere river. The Zêzere River is an important riverand is under the Cabeço do Pião tailings influence. The knowledge and methods acquired will lead to aconceptual model working as guidance to a more sustainable mining in the hereafter.